Life Cycle Assessment Kerangka Hand Sanitizer Pedal - Daniel Alfrentino Ngabuk; Jemmy Immanuel; Desrina Yusi Irawati (Universitas Katolik Darma Cendika, 2022)
Life Cycle Assessment (LCA) is a method used to analyze the impact of a product on the environment during the product life cycle. LCA itself can also be said as an approach to measure the environmental impact caused by company activities, then the production process, and finally waste management. LCA aims to make a study of the impact of recycling a product on the area and provide detailed data for the consumption of materials and energy during the creation period. There are several benefits from implementing this LCA, namely saving energy and raw materials, cheaper distribution costs, and many more benefits from implementing this LCA, especially in companies whose products produce quite a lot of waste. At the LCA stage, the entire series in the product life cycle is always considered. In research activities, LCA is an added value to provide information on the environmental impacts that occur from the research process and then produce the product of the research itself.